Management Turnover Through Deaths of Key Executives: Effects on Investor Wealth - Worrell, Dan L.; Davidson, Wallace N.; Chandy, P. R.; Garrison, Sharon (Academy of Management Journal, 1986)
As an initial step in redirecting research on turnover to focus on its consequences, this study examined the reaction of the securities' market to the deaths of certain key executives. Although death had little influence on the market for the population studied as a whole, when key executives were differentiated by position, significant differences did occur. Negative abnormal returns were also found to be associated with name recognition and suddenness of executives' deaths.